Analisis Tingkat Perputaran Piutang pada PT.PLN (Persero) Unit Layanan Pelanggan (ULP) Lubuk Alung Tahun 2019 - Z Zulhendra (SAFE-Network, 2023)
Manage recei vables gi ven, which can be seen from the ratio of receivables activity where this ratio meas ures the effectiveness of the company in collecting recei vables. The recei vable activity ratio consists of recei vables turnover and t he average peri od of collection of recei vables. This type of research is a simple applied research with quantitative descriptive analysis technique that describes the level of receivables turnover and the effectiveness of collecting receivables PT.PLN (Persero) Lubuk Alung Customer Service Unit. The data in this study uses secondary data in the form of an overview report of the balance of receivables obtained indirectly from the object of research. Based on the results of the study, it was found that in 2019, the receivable turnover rate of PT PLN (Persero) Lubuk Alung Customer Service Unit in the first quarter of the receivables turnover was 4 times and the receivables collection period was 10 days, the second quarter the receivables turnover was 3 times and the collection period was 10 days. 12 days, 3rd quarter of receivables collection and collection period of 13 days, 4th quarter of receivables collection 3 times and collection period of 11 days. The effectiveness of the receivables turnover of PT PLN (Persero) Lubuk Alung Customer Service Unit in collecting receivables is quite good because it is still under the conditions determined by the company between 10-15 days.